Electrode, oxygen sensor and electrode preparation method

By using macrocyclic metal coordination compounds with strong electron-absorbing groups as catalyst materials in the oxygen sensor electrode, the problem of side reactions caused by high overpotential of the oxygen sensor is solved, and the effect of improving linearity and sensitivity is achieved.

CN119827598APending Publication Date: 2025-04-15SHENZHEN MEIHAO CHUANGYI MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411969296.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing oxygen sensors have a higher overpotential when reacting with oxygen, which increases the difficulty of reaction and is prone to trigger side reactions, such as hydrogen evolution reactions, interfering with oxygen signals, and affecting linearity and sensitivity.

Method used

A macrocyclic metal coordination compound with strong electron-absorbing groups is used as a catalyst material to reduce the working potential of the electrode reacting with oxygen, thereby reducing the occurrence of side reactions.

Benefits of technology

By reducing the overpotential, the linearity and sensitivity of the oxygen sensor are improved, the generation of side reaction currents are reduced, and the accuracy of detecting oxygen concentration is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827598A_ABST
    Figure CN119827598A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical sensors, in particular to an electrode, an oxygen sensor and an electrode preparation method, the electrode comprises a gas-permeable membrane and a catalyst layer, the catalyst layer comprises a metal material, a carbon material and a catalyst material, the catalyst material adopts a macrocyclic metal coordination compound with a strong electron withdrawing group, the macrocyclic metal coordination compound comprises macrocyclic molecules and coordination metal ions. The electrode is used as the cathode of the oxygen sensor, and the linearity and the sensitivity of the oxygen sensor for testing the oxygen concentration can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrochemical sensors, and in particular to an electrode, an oxygen sensor, and a method for preparing the electrode. Background Art

[0002] Galvanic cell oxygen sensor is a type of electrochemical oxygen sensor, which is widely used in oxygen testing devices to detect oxygen concentration. The reaction principle is that oxygen undergoes an oxidation-reduction reaction at the anode and cathode, ionizing the anode metal and releasing electrons. The current is proportional to the oxygen concentration. At present, the galvanic cell oxygen sensor in the relevant technology is usually composed of an anode, a cathode and an electrolyte. The anode is usually made of metal materials with a large ionization tendency such as lead, cadmium, tin, and antimony. The cathode is usually made of metal materials such as platinum, palladium, silver, and copper. The electrolyte is usually an alkaline electrolyte. Correspondingly, the reaction formula of the working process of the galvanic cell oxygen sensor is as follows: Anode: 2M+4OH - =2MO+2H2O+4e - ; Cathode: O2+H2O+4e - =4OH - ; Wherein, M is the anode metal material.

[0003] Ideally, the working potential required by the oxygen sensor during its reaction with oxygen is the theoretical equilibrium potential for the reaction to occur in an equilibrium state. However, in actual reactions, it is often necessary to overcome resistances such as activation resistance and charge transfer resistance, which causes the working potential to show a value higher than the theoretical equilibrium potential. The voltage that exceeds the theoretical value is called overpotential.

[0004] The existence of overpotential makes the actual working potential of the oxygen sensor reacting with oxygen higher than the theoretical equilibrium potential of the theoretical reaction. The larger the overpotential, the more difficult it is for the oxygen sensor to react, and the easier it is to cause other side reactions, such as hydrogen evolution reaction (hydrogen evolution reaction is the reduction reaction of hydrogen ions in water into hydrogen gas). This type of side reaction will generate side reaction current, which will interfere with the real oxygen signal current of the oxygen sensor, thereby affecting the linearity and sensitivity of the sensor in testing oxygen concentration. Summary of the invention

[0005] One of the purposes of the present application is to provide an electrode which uses a macrocyclic metal coordination compound with a strong electron-withdrawing group as a catalyst material, and can reduce the working potential of the electrode for actual reaction with oxygen.

[0006] The second purpose of the present application is to provide an oxygen sensor, which is prepared using the above-mentioned electrode and can reduce the generation of side reaction current during the use of the oxygen sensor, thereby improving the linearity and sensitivity of the oxygen sensor in testing oxygen concentration.

[0007] The third purpose of the present application is to provide an electrode preparation method, wherein the prepared electrode is used to prepare an oxygen sensor, which can reduce the generation of side reaction current during the application of the oxygen sensor, thereby improving the linearity and sensitivity of the oxygen sensor in testing oxygen concentration.

[0008] One of the purposes of this application is achieved by the following technical solution:

[0009] An electrode comprises a gas permeable membrane and a catalyst layer, wherein the catalyst layer comprises a metal material, a carbon material and a catalyst material, wherein the catalyst material adopts a macrocyclic metal coordination compound with a strong electron-withdrawing group, and the macrocyclic metal coordination compound comprises a macrocyclic molecule and a coordinated metal ion.

[0010] Theoretically, the smaller the overpotential, the easier it is for the corresponding redox reaction to occur; the catalytic activity of the catalytic layer can be improved to reduce the overpotential in the actual reaction, so as to achieve the purpose of improving the overall performance of the sensor. Metal platinum-based materials are catalyst materials that can effectively improve the catalytic activity of the catalytic layer, but their high prices limit large-scale commercial use. The electrode in this technical solution uses a macrocyclic metal coordination compound with a strong electron-withdrawing group as a catalyst material. The strong electron-withdrawing group on the macrocyclic metal coordination compound can promote the combination of the macrocyclic molecule and the hydroperoxide functional group (OOH*) intermediate, so that the macrocyclic metal coordination compound is easy to reduce and can form a catalytically active substance at a lower potential. The catalytically active substance formed can reduce the working potential of the electrode and oxygen to actually react, thereby reducing the overpotential when the reaction actually occurs at this oxygen concentration; the use of this electrode to prepare an oxygen sensor can reduce the occurrence of side reactions (such as hydrogen evolution reactions) caused by excessive overpotentials and the generation of side reaction currents, thereby improving the linearity and sensitivity of the oxygen sensor in testing oxygen concentration.

[0011] Furthermore, the macrocyclic metal coordination compound is a metal porphyrin or a metal phthalocyanine.

[0012] Furthermore, the strong electron withdrawing group is one of a tertiary amine cation, a nitro group and a halide group.

[0013] The second purpose of this application is achieved by the following technical solution:

[0014] An oxygen sensor comprises an anode, a cathode and an electrolyte, wherein the cathode adopts the electrode mentioned above.

[0015] By adopting the above technical scheme, in the application process of the oxygen sensor to test the oxygen concentration, the strong electron-withdrawing group on the macrocyclic metal coordination compound can promote the combination of the macrocyclic molecule and the hydroperoxide functional group (OOH*) intermediate, so that the macrocyclic metal coordination compound is easy to reduce and can form a catalytically active substance at a lower potential. The formed catalytically active substance can reduce the working potential of the electrode and oxygen to actually react, thereby reducing the overpotential when the actual reaction occurs at the oxygen concentration, thereby reducing the occurrence of side reactions (such as hydrogen evolution reaction) caused by excessive overpotential and the generation of side reaction currents, thereby achieving the effect of improving the linearity and sensitivity of the oxygen sensor to test the oxygen concentration.

[0016] The third purpose of this application is achieved by the following technical solution:

[0017] A method for preparing an electrode comprises the following steps:

[0018] Obtaining a slurry; wherein the slurry comprises a uniformly mixed metal material, a carbon material, a macrocyclic metal coordination compound and a perfluorosulfonic acid resin dispersion, the metal material and the carbon material are both powder materials, the macrocyclic metal coordination compound has a strong electron-withdrawing group, and the macrocyclic metal coordination compound comprises a macrocyclic molecule and a coordinated metal ion;

[0019] The electrode is obtained, and the slurry is scraped onto a hydrophobic breathable membrane, and dried to obtain a target electrode.

[0020] By adopting the above technical solution, the prepared electrode is used to prepare an oxygen sensor, which can reduce the generation of side reaction current during the application of the oxygen sensor, thereby improving the linearity and sensitivity of the oxygen sensor in testing oxygen concentration.

[0021] Furthermore, the macrocyclic metal coordination compound is a metal porphyrin or a metal phthalocyanine.

[0022] Furthermore, the strong electron withdrawing group is one of a tertiary amine cation, a nitro group and a halide group.

[0023] Furthermore, the metal material is one of copper, platinum, palladium and silver; and / or the carbon material is carbon nanotubes.

[0024] Furthermore, the perfluorosulfonic acid resin dispersion comprises a perfluorosulfonic acid resin and an organic solvent, and the weight content of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion is 2 wt % to 20 wt %.

[0025] Furthermore, the macrocyclic metal coordination compound having the strong electron-withdrawing group is perchlorophthalocyanine cobalt or tetrakis-p-chlorophenylporphyrin iron.

[0026] Furthermore, the perfluorosulfonic acid resin dispersion includes a perfluorosulfonic acid resin and an organic solvent. In the dried product obtained by drying the slurry, the content of the metal material is 30% to 90%, the content of the carbon material is 5% to 50%, the content of the macrocyclic metal coordination compound is 0.1% to 20%, and the content of the perfluorosulfonic acid resin is 0.5% to 30%.

[0027] In summary, this application at least includes the following beneficial technical effects:

[0028] This scheme uses a macrocyclic metal coordination compound as an electrode catalyst material. The strong electron-withdrawing group on the macrocyclic metal coordination compound can promote the combination of the macrocyclic molecule and the hydroperoxide functional group (OOH*) intermediate, so that the macrocyclic metal coordination compound is easy to reduce and can form a catalytically active substance at a lower potential. The formed catalytically active substance can reduce the working potential of the electrode for the actual reaction with oxygen, thereby reducing the overpotential when the actual reaction occurs under the oxygen concentration; the use of the electrode to prepare an oxygen sensor can reduce the occurrence of side reactions (such as hydrogen evolution reaction) caused by excessive overpotential and the generation of side reaction currents, thereby achieving the effect of improving the linearity and sensitivity of the oxygen sensor in testing oxygen concentration. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is an open circuit potential curve diagram of different sensors corresponding to different oxygen concentrations in the embodiments of the present application;

[0030] Figure 2 It is a linear fitting diagram of different sensors in the embodiments of the present application. DETAILED DESCRIPTION

[0031] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0032] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0033] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0034] Under ideal conditions, the working potential required by the oxygen sensor in the process of reacting with oxygen is the theoretical equilibrium potential of the reaction in the equilibrium state. In actual reactions, it is often necessary to overcome resistances such as activation resistance and charge transfer resistance, so that the working potential will show a value higher than the theoretical equilibrium potential. The voltage exceeding the theoretical value is called overpotential. The existence of overpotential makes the working potential of the oxygen sensor actually reacting with oxygen higher than the theoretical equilibrium potential of the theoretical reaction. The larger the overpotential, the more difficult it is for the oxygen sensor to react, and the more likely it is to cause other side reactions, such as hydrogen evolution reaction (hydrogen evolution reaction is the reduction reaction of hydrogen ions in water to hydrogen gas). This type of side reaction will generate side reaction current, which will interfere with the real oxygen signal current of the oxygen sensor, thereby affecting the linearity and sensitivity of the sensor to test oxygen concentration. In theory, the smaller the overpotential, the easier it is for the corresponding redox reaction to occur; the overpotential in the actual reaction can be reduced by improving the catalytic activity of the catalytic layer.

[0035] An embodiment of the present application discloses an electrode, which includes a breathable membrane and a catalytic layer, wherein the catalytic layer is a layered structure in which multiple materials are evenly mixed, and the catalytic layer specifically includes a metal material, a carbon material and a catalyst material, and the catalyst material adopts a macrocyclic metal coordination compound with a strong electron-withdrawing group, and the macrocyclic metal coordination compound includes a macrocyclic molecule and a coordinated metal ion.

[0036] The electrode adopts a macrocyclic metal coordination compound with a strong electron-withdrawing group as a catalyst material. The strong electron-withdrawing group on the macrocyclic metal coordination compound can promote the combination of the macrocyclic molecule and the hydroperoxide functional group (OOH*) intermediate, so that the macrocyclic metal coordination compound is easy to reduce and can form a catalytic active substance at a lower potential. The formed catalytic active substance can reduce the working potential of the electrode and oxygen to actually react, thereby reducing the overpotential when the actual reaction occurs under the oxygen concentration; the preparation of an oxygen sensor using the electrode can reduce the occurrence of side reactions (such as hydrogen evolution reactions) caused by excessive overpotential and the generation of side reaction currents, thereby achieving the effect of improving the linearity and sensitivity of the oxygen sensor in testing oxygen concentration.

[0037] In some embodiments, the macrocyclic metal coordination compound uses metal porphyrin or metal phthalocyanine; in some specific examples, the macrocyclic metal coordination compound uses porphyrin iron, wherein the macrocyclic molecule is a porphyrin molecule and the coordinated metal ion is an iron ion; in other specific examples, the macrocyclic metal coordination compound uses cobalt phthalocyanine, wherein the macrocyclic molecule is a phthalocyanine molecule and the coordinated metal ion is a cobalt ion.

[0038] In some embodiments, the strong electron withdrawing group is one of a tertiary amine cation, a nitro group and a halide group; in some specific examples, the strong electron withdrawing group is a halide group, for example, the macrocyclic metal coordination compound is perchlorophthalocyanine cobalt or tetrakis-p-chlorophenylporphyrin iron.

[0039] In some embodiments, the metal material is one of copper, platinum, palladium and silver. Specifically, in this embodiment, the metal material is copper. In some embodiments, the carbon material is carbon nanotubes. Specifically, in this embodiment, the carbon nanotubes have an outer diameter of 20 nm and a specific surface area of ​​300 m 2 / g.

[0040] The present application also discloses an oxidation sensor, which includes an anode, a cathode, and an electrolyte, wherein the anode is made of a metal material with a large ionization tendency such as lead, cadmium, tin, and antimony, the cathode is the electrode mentioned above, and the electrolyte is an alkaline electrolyte. In some specific embodiments, the anode is a tin metal anode, and the electrolyte is a potassium hydroxide electrolyte.

[0041] The embodiment of the present application also discloses a method for preparing an electrode, and the preparation scheme includes the following steps.

[0042] S01. Obtain slurry.

[0043] The slurry includes uniformly mixed metal material, carbon material, macrocyclic metal coordination compound and perfluorosulfonic acid resin dispersion, the metal material and carbon material are both powder materials, the macrocyclic metal coordination compound has a strong electron-withdrawing group, and the macrocyclic metal coordination compound includes macrocyclic molecules and coordinated metal ions.

[0044] It should be noted that the slurry may be made of prefabricated materials or may be directly prepared; accordingly, in some embodiments of preparing the slurry, the following steps are included:

[0045] S011. Prepare a perfluorosulfonic acid resin dispersion; wherein the solute of the perfluorosulfonic acid resin dispersion is perfluorosulfonic acid resin and the solvent is ethylene glycol.

[0046] S012. Add metal material, carbon material and macrocyclic metal coordination compound into a container, add perfluorosulfonic acid resin dispersion, and stir evenly.

[0047] S02. Obtain electrodes.

[0048] The slurry is scraped onto a hydrophobic breathable membrane and dried at a temperature of 40° C. to 150° C. to obtain a target electrode.

[0049] In some embodiments, the macrocyclic metal coordination compound uses metal porphyrin or metal phthalocyanine; in some specific examples, the macrocyclic metal coordination compound uses porphyrin iron, wherein the macrocyclic molecule is a porphyrin molecule and the coordinated metal ion is an iron ion; in other specific examples, the macrocyclic metal coordination compound uses cobalt phthalocyanine, wherein the macrocyclic molecule is a phthalocyanine molecule and the coordinated metal ion is a cobalt ion.

[0050] In some embodiments, the strong electron withdrawing group is one of a tertiary amine cation, a nitro group and a halide group; in some specific examples, the strong electron withdrawing group is a halide group, for example, the macrocyclic metal coordination compound is configured as perchlorophthalocyanine cobalt or tetrakis-p-chlorophenylporphyrin iron.

[0051] In some embodiments, the metal material is one of copper, platinum, palladium and silver. Specifically, in this embodiment, the metal material is copper. In some embodiments, the carbon material is carbon nanotubes. Specifically, in this embodiment, the carbon nanotubes have an outer diameter of 20 nm and a specific surface area of ​​300 m 2 / g.

[0052] In some embodiments, the perfluorosulfonic acid resin dispersion includes a perfluorosulfonic acid resin and an organic solvent, and the weight content percentage of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion is 2wt% to 20wt%. In some specific examples, the weight content percentage of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion can be configured to be 5wt%, 8wt%, or 18wt%.

[0053] In some embodiments, the perfluorosulfonic acid resin dispersion includes a perfluorosulfonic acid resin and an organic solvent. In the dried product obtained by drying the slurry, the content of the metal material is 30% to 90%, the content of the carbon material is 5% to 50%, the content of the macrocyclic metal coordination compound is 0.1% to 20%, and the content of the perfluorosulfonic acid resin is 0.5% to 30%. In some examples, the content ratio of the metal material, the carbon material, the macrocyclic metal coordination compound and the perfluorosulfonic acid resin is 75:15:3:10; in other examples, the content ratio of the metal material, the carbon material, the macrocyclic metal coordination compound and the perfluorosulfonic acid resin is 72:15:3:10; in other examples, the content ratio of the metal material, the carbon material, the macrocyclic metal coordination compound and the perfluorosulfonic acid resin is 70:15:5:10. At the same time, in the above specific examples, the sum of the contents of metal materials, carbon materials, macrocyclic metal coordination compounds and perfluorosulfonic acid resins can be 100%; or the sum of the contents of metal materials, carbon materials, macrocyclic metal coordination compounds and perfluorosulfonic acid resins can be less than 100%, which indicates that the dried product obtained by drying the slurry also contains other substances.

[0054] Some specific examples and comparative examples are provided below.

[0055] Example 1

[0056] Prepare a perfluorosulfonic acid resin dispersion for use; wherein the perfluorosulfonic acid resin dispersion solvent is 5wt% perfluorosulfonic acid resin, and the solvent is ethylene glycol. Weigh 0.75g of copper metal powder, the purity of which is 99.99%; weigh 0.15g of carbon nanotubes, the outer diameter of which is 20nm and the specific surface area is 300m 2 / g; weigh 0.03g of perchlorophthalocyanine cobalt. Put copper metal powder, carbon nanotubes and perchlorophthalocyanine cobalt in a beaker, and then slowly add 2g of perfluorosulfonic acid resin mother solution while stirring for 12 hours to prepare a slurry. The slurry was coated on a polytetrafluoroethylene film and dried in an oven at 120°C to obtain electrode No. 1.

[0057] Comparative Example 1

[0058] Prepare a perfluorosulfonic acid resin dispersion for use; wherein the perfluorosulfonic acid resin dispersion solvent is 5wt% perfluorosulfonic acid resin, and the solvent is ethylene glycol. Weigh 0.75g of copper metal powder, the purity of which is 99.99%; weigh 0.15g of carbon nanotubes, the outer diameter of which is 20nm and the specific surface area is 300m 2 / g. Copper metal powder and carbon nanotubes were placed in a beaker, and then 2g of perfluorosulfonic acid resin mother solution was slowly added while stirring for 12 hours to prepare a slurry. The slurry was coated on a polytetrafluoroethylene film and dried in an oven at 120°C to obtain electrode No. 2.

[0059] Example 2

[0060] Prepare a perfluorosulfonic acid resin dispersion for use; wherein the perfluorosulfonic acid resin dispersion solvent is 5wt% perfluorosulfonic acid resin, and the solvent is ethylene glycol. Weigh 0.75g of copper metal powder, the purity of which is 99.99%; weigh 0.15g of carbon nanotubes, the outer diameter of which is 20nm and the specific surface area is 300m 2 / g; weigh 0.03g of tetrachlorophenylporphyrin iron. Put copper metal powder, carbon nanotubes and tetrachlorophenylporphyrin iron in a beaker, and then slowly add 2g of perfluorosulfonic acid resin mother solution while stirring for 12 hours to prepare a slurry. Coat the slurry on a polytetrafluoroethylene film and dry it in an oven at 120°C to obtain electrode No. 3.

[0061] Comparative Example 2

[0062] Prepare a perfluorosulfonic acid resin dispersion for use; wherein the perfluorosulfonic acid resin dispersion solvent is 5wt% perfluorosulfonic acid resin, and the solvent is ethylene glycol. Weigh 0.75g of copper metal powder, the purity of which is 99.99%; weigh 0.15g of carbon nanotubes, the outer diameter of which is 20nm and the specific surface area is 300m 2 / g; weigh 0.03g of cobalt phthalocyanine. Put copper metal powder, carbon nanotubes and cobalt phthalocyanine in a beaker, and then slowly add 2g of perfluorosulfonic acid resin mother solution while stirring for 12 hours to prepare a slurry. Coat the slurry on a polytetrafluoroethylene film and dry it in an oven at 120°C to obtain a No. 4 electrode.

[0063] Comparative Example 3

[0064] Prepare a perfluorosulfonic acid resin dispersion for use; wherein the perfluorosulfonic acid resin dispersion solvent is 5wt% perfluorosulfonic acid resin, and the solvent is ethylene glycol. Weigh 0.75g of copper metal powder, the purity of which is 99.99%; weigh 0.15g of carbon nanotubes, the outer diameter of which is 20nm and the specific surface area is 300m 2 / g; weigh 0.03g of porphyrin ferrous iron. Put copper metal powder, carbon nanotubes and porphyrin ferrous iron in a beaker, then slowly add 2g of perfluorosulfonic acid resin mother solution while stirring for 12 hours to prepare a slurry. Coat the slurry on a polytetrafluoroethylene film and dry it in an oven at 120°C to obtain a No. 5 electrode.

[0065] The electrodes in the above Example 1, Comparative Example 1, Example 2, Comparative Example 2 and Comparative Example 3 are used as cathodes to assemble oxygen sensors No. 1 to No. 5, as follows:

[0066] Sensor No. 1 includes a cathode, an anode and an electrolyte, wherein the cathode uses the No. 1 electrode prepared in Example 1, the anode uses a tin metal anode, and the electrolyte uses a potassium hydroxide electrolyte containing 15 wt% potassium hydroxide.

[0067] Sensor No. 2 includes a cathode, an anode and an electrolyte, wherein the cathode uses the No. 2 electrode prepared in Comparative Example 1, the anode uses a tin metal anode, and the electrolyte uses a potassium hydroxide electrolyte containing 15 wt% potassium hydroxide.

[0068] Sensor No. 3 includes a cathode, an anode and an electrolyte, wherein the cathode uses the No. 3 electrode prepared in Example 2, the anode uses a tin metal anode, and the electrolyte uses a potassium hydroxide electrolyte containing 15 wt% potassium hydroxide.

[0069] Sensor No. 4 includes a cathode, an anode and an electrolyte, wherein the cathode uses the No. 4 electrode prepared in Comparative Example 2, the anode uses a tin metal anode, and the electrolyte uses a potassium hydroxide electrolyte containing 15 wt% potassium hydroxide.

[0070] Sensor No. 5 includes a cathode, an anode and an electrolyte, wherein the cathode uses the No. 5 electrode prepared in Comparative Example 3, the anode uses a tin metal anode, and the electrolyte uses a potassium hydroxide electrolyte containing 15 wt% potassium hydroxide.

[0071] The above five sensors were tested: the sensor was placed in a sealed device. The test environment at this time was air (20.95% oxygen). Then nitrogen, 60% oxygen and 100% pure oxygen were introduced in turn, and the open circuit potential (Open Circuit Potential) signal of the sensor was monitored. The open circuit potential data table of the sensor at different oxygen concentrations was shown in the following table.

[0072]

[0073] Based on the above open circuit potential data table, the open circuit potential curve of the sensor corresponding to different oxygen concentrations is drawn as shown in the figure Figure 1 As shown, further calculations to obtain the sensitivity data of the sensor are shown in the following table.

[0074]

[0075] It should be noted that the sensitivity of the above-mentioned sensor refers to the sensor's ability to respond to the input signal, usually expressed as the ratio between the change in the output signal and the change in the input signal. Sensitivity reflects the sensor's ability to detect small changes and is one of the important parameters to measure its performance. Among them, the sensitivity of the above-mentioned sensor refers to the ratio between the sensor's open circuit potential to the target gas and the gas concentration.

[0076] Based on the open circuit potential data table obtained from the above test, the linear fitting diagram of the sensor is drawn as follows: Figure 2 As shown, in Figure 2 The corresponding fitting straight line equation based on the linear fitting graph is presented in 2 The data is shown in the following table.

[0077] serial number Sensor No. 1 Sensor No. 2 Sensor No. 3 Sensor No. 4 Sensor No. 5 <![CDATA[Relevant Index R 2 > 1 0.9992 1 0.9985 0.9958

[0078] It should be noted that the linear correlation index R 2 It indicates the degree of correlation between the actual value obtained by the test and the theoretical predicted value. The calculation formula is: Among them, y i is the actual value obtained by the test, is the average of the actual values ​​obtained in the test, It is the theoretical prediction value calculated based on the fitted straight line equation. And the correlation coefficient R 2 The closer it is to 1, the better the linearity of the sensor, that is, the smaller the deviation between the actual value obtained from the test and the theoretical predicted value.

[0079] Combined with the above data table and Figure 1 , Figure 2 The following conclusions can be obtained:

[0080] (1) The linearity and sensitivity of sensor No. 1 and sensor No. 3 are better than those of sensor No. 2, sensor No. 4 and sensor No. 5, indicating that adding a macrocyclic metal coordination compound with a strong electron-withdrawing group (such as perchlorophthalocyanine cobalt in Example 1 and tetrakis(p-chlorophenyl)porphyrin iron in Example 2) to the electrode serving as the sensor cathode can improve the linearity and sensitivity of the sensor.

[0081] (2) The linearity and sensitivity of sensor No. 1 are better than those of sensor No. 4, and the linearity and sensitivity of sensor No. 2 are better than those of sensor No. 5, indicating that the strong electron-withdrawing groups in the macrocyclic metal coordination compounds with strong electron-withdrawing groups in the electrode are the main factors for improving the linearity and sensitivity of the sensor.

[0082] (3) The sensitivity of sensor No. 4 and sensor No. 5 is higher than that of sensor No. 2, but their linearity is lower than that of sensor No. 2, indicating that adding a macrocyclic metal coordination compound without a strong electron-withdrawing group to the electrode serving as the sensor cathode can improve the sensitivity of the sensor to a certain extent, but will reduce the linearity of the sensor.

[0083] In summary, the electrode used for the cathode of the oxygen sensor uses a macrocyclic metal coordination compound with a strong electron-withdrawing group as a catalyst material, which can improve the linearity and sensitivity of the oxygen sensor in testing oxygen concentration.

[0084] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An electrode, characterized in that: The invention comprises a breathable membrane and a catalytic layer, wherein the catalytic layer comprises a metal material, a carbon material and a catalyst material, and the catalyst material adopts a macrocyclic metal coordination compound with a strong electron-withdrawing group, and the macrocyclic metal coordination compound comprises a macrocyclic molecule and a coordinated metal ion.

2. The electrode according to claim 1, characterized in that The macrocyclic metal coordination compound adopts metal porphyrin or metal phthalocyanine.

3. The electrode according to claim 1, characterized in that The strong electron withdrawing group is one of a tertiary amine cation, a nitro group and a halide group.

4. An oxygen sensor, characterized in that: The invention comprises an anode, a cathode and an electrolyte, wherein the cathode adopts the electrode according to any one of claims 1 to 3.

5. A method for preparing an electrode, characterized in that: The following steps are involved: Obtaining a slurry; wherein the slurry comprises a uniformly mixed metal material, a carbon material, a macrocyclic metal coordination compound and a perfluorosulfonic acid resin dispersion, the metal material and the carbon material are both powder materials, the macrocyclic metal coordination compound has a strong electron-withdrawing group, and the macrocyclic metal coordination compound comprises a macrocyclic molecule and a coordinated metal ion; The electrode is obtained, and the slurry is scraped onto a hydrophobic breathable membrane, and dried to obtain a target electrode.

6. The electrode preparation method according to claim 5, characterized in that: The macrocyclic metal coordination compound is a metal porphyrin or a metal phthalocyanine; and / or the strong electron withdrawing group is one of a tertiary amine cation, a nitro group and a halogenated group.

7. The electrode preparation method according to claim 5, characterized in that: The metal material is one of copper, platinum, palladium and silver; and / or the carbon material is carbon nanotubes.

8. The electrode preparation method according to claim 5, characterized in that: The perfluorosulfonic acid resin dispersion comprises a perfluorosulfonic acid resin and an organic solvent, and the weight content of the perfluorosulfonic acid resin in the perfluorosulfonic acid resin dispersion is 2wt% to 20wt%.

9. The electrode preparation method according to claim 5, characterized in that: The macrocyclic metal coordination compound having the strong electron-withdrawing group is perchlorophthalocyanine cobalt or tetrakis-p-chlorophenylporphyrin iron.

10. The electrode preparation method according to claim 5, characterized in that: The perfluorosulfonic acid resin dispersion includes perfluorosulfonic acid resin and an organic solvent. In the dried product obtained by drying the slurry, the content of the metal material is 30% to 90%, the content of the carbon material is 5% to 50%, the content of the macrocyclic metal coordination compound is 0.1% to 20%, and the content of the perfluorosulfonic acid resin is 0.5% to 30%.